ANALYSIS OF THE REQUIREMENTS OF INTERNATIONAL AND NATIONAL STANDARDS FOR MEASUREMENT METHODS AND METROLOGICAL EQUIPMENT - Roman Trishch; Olga Maletska; Olena Cherniak; Julija Semionova; Vladislav Jancis (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of research in the article are methods and means of measurement and testing. The goal of the work is to analyze the metrological requirements of the ISO/IEC 17025:2017 standard for equipment and methods used to conduct tests in laboratories to ensure control of the metrological system processes, and to provide information on the practical application of the requirements of this standard, taking into account the provisions of other international standards. The following tasks are solved in the article: analysis of the position of international documents containing the requirements to the equipment and test methods for measurement in order to determine their practical implementation; analysis of ISO/IEC 17025:2017 on metrological requirements and proposed ways of implementation of these requirements. The following methods are used - analysis method. The following results have been obtained: the analysis of international requirements to the equipment, including measuring, testing (measurement) and standardization of these requirements has been carried out to implement the provisions of ISO/IEC 17025:2017. An important factor in the implementation of the standard in Ukraine is that currently there are no national standards that would regulate the general requirements for the use of measuring equipment and assess the accuracy of measurement results. This standard provides general approaches to the use of equipment and accuracy characteristics of the results obtained by appropriate methods. Fulfillment of the requirements of the methodology makes it possible to obtain a reliable result with the required accuracy. Conclusions: on the basis of the carried out analysis it is established that ISO/IEC 17025:2017 became a new perspective step towards application of metrological requirements to means and methods of testing and measurements defined by various other international documents in the field of metrology; the standard is a fundamental, in fact, reference book for metrologists on organization of work on assurance of reliability of measurement results and tests at the enterprise; assurance of conformity to the requirements of the international standard provides customers with confidence in the results of measurements.